2018
DOI: 10.1016/j.rmcr.2018.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix fistula plug for repair of bronchopleural fistula

Abstract: IntroductionBronchopleural fistula (BPF) is a feared complication of pulmonary resection. Fistula plugs (FP) have been described as an adequate treatment in anorectal disease. We describe our early experience placing an FP in the treatment of BPF.Materials and methodsWe retrospectively reviewed 5 patients for whom a FP was placed for BPF at our institution. Demographic data, initial perioperative information, method and technique of FP placement, and success is reported.ResultsFive patients (4 male, 1 female) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Fistula plugs function as a framework for fibroblasts, fostering natural tissue growth, facilitating cellular proliferation and tissue healing, and aiding in the repair of damaged tissues. Sakata et al [ 30 ] reported the use of flexible bronchoscopy to place FPs in 5 patients with BPF. Among them, 3 patients completely stopped air leakage within 4 days and 1 patient significantly reduced air leakage, thereby achieving success.…”
Section: Progress Reportmentioning
confidence: 99%
“…Fistula plugs function as a framework for fibroblasts, fostering natural tissue growth, facilitating cellular proliferation and tissue healing, and aiding in the repair of damaged tissues. Sakata et al [ 30 ] reported the use of flexible bronchoscopy to place FPs in 5 patients with BPF. Among them, 3 patients completely stopped air leakage within 4 days and 1 patient significantly reduced air leakage, thereby achieving success.…”
Section: Progress Reportmentioning
confidence: 99%